Covid-19: Can Halal Food Lessen the Risks of the Next Similar Outbreak? - Fatya Alty Amalia; Kung Jeng Wang; Arie Indra Gunawan (Jurnal Internasional Penelitian Bisnis Terapan, 2020)
As COVID-19 is a zoonosis virus that involves wildlife as its primary host (i.e. bat) like the previous outbreaks (SARS and MERS), it is prudent to reduce the transmission risk from wildlife consumption. Such an approach should be enforced to mitigate the risk of a future outbreak akin to COVID-19. However apparently, it is not a simple task to change such a consumption culture in a short time, though the devastating socio-economic impacts obviously have been yielded. Concerned with the current outbreak impacts, this study attempts to propose a prophylactic strategy through Halal food, an Islamic diet tradition, as a way to lessen the risk of a future outbreak akin to COVID-19. Tayyib(wholesome) principle which is often associated with Halal food can make Halal food not only â€œpermissibleâ€ upon Islamic teaching but also â€œgoodâ€ and â€œcleanâ€ to consume. As Tayyibredefines the conventional Halal food concept, it underlines more strongly on the medical facet of Halal food, i.e. food safety and health. According to Islamic teaching, Halal food encourages the consumption of domestic animals and more plant-based food. Meanwhile at the same time, it also heavily establishes the procedures of food safety and maintains the integrity of its credence status. Based on these, this study claims that more Halal food consumptions can lessen the risk of future outbreaks like COVID-19.